Influência de um programa de iniciação esportiva em crianças com deficiência física - Melo, Flávio Anderson Pedrosa de (2014)
To reflect about the need for development of motor abilities to any individual, and considering that most of children with physical disabilities are partially or totally privates of the exploration of their bodies and diversified motor experiences, emerged the ideal of systematization of a program of sporting initiation, using itself games and play with goal of developing the fundamental motor abilities (stabilizers, locomotors, manipulative) aimed at sporting initiation. Thus, this study had as goal to check the influence of a sporting initiation program in the development of fundamental motor abilities of children with physical disabilities. Specifically, we seek to elaborate, apply and describe a sporting initiation program directed to children with physical disabilities; to establish criteria/ parameters for evaluation of fundamental motor abilities of children with physical disabilities contextualized in a sporting initiation program; to verify in which areas of fundamental motor abilities of children with physical disabilities the program exercised greater or lesser influence, before and after the proposed intervention. This is a study of quali-quantitative approach, it characterized as research field, of type quantitative-descriptive directed to "study of evaluation of the program". The study sample was incorporated for three children with physical disabilities, of both genders (2 M and 1 F) and age range between six and ten years old. The instruments of data collection utilized were the systematic observation (the tab) and Evaluation Protocol of Sporting Initiation (PAIE) that was developed by the researcher as a means of evaluating the program and the evolution of the participants. The research was divided in four steps: 1) The achievement the anamnesis 2) The application of initial evaluation 3) The development of the program of sporting initiation for children with physical disabilities, which lasted eight weeks, three sessions / lessons per weeks, for a total of twenty four sessions in a period of two-month of intervention. Each one of sessions was planned with average duration of fifty minutes; 4) The application of final evaluation. As a way of analysis of the data obtained by means of the protocol, it was utilized descriptive statistic analysis; the field diary was interpreted in the light of content analysis. The suggested and employee instrument as parameters for evaluation pre and post intervention (PAIE) was sensitive for the characteristics of the children with physical disabilities participating in the study; being able to check the involved variables in the program. Analysis of the results showed that the involved participants in the study (n=3) obtained improvements in each one of three fundamental motor abilities. It was possible to conclude that in general, the program of sporting initiation directed for children with physical disabilities was efficient for the development these abilities.